The Impact of Academic Procrastination on Second Language Writing: The Mediating Role of L2 Writing Anxiety - Zhang, Chen; Zhang, Wenzhong (Frontiers in Psychology, 2022)
Recently, there has been a surge of interest in the exploration of psychological properties in a second language context. Considerable literature has grown up around the influence of these psychological properties on L2 writing specifically. However, the impact of academic procrastination, which is an important psychological property, has been understudied and it remains unclear how affective factors in L2 might play a role in the above potential influence on L2 writing. Therefore, the current study explored the impact of academic procrastination on L2 writing and examined the mediating role of L2 writing anxiety, by adopting text readability as an innovative approach to assessing L2 writing performance. Participants were 55 Chinese speakers of L2 English. By utilizing the collected questionnaire data and the readability indicators of the L2 writing task, the current research conducted correlation analysis, regression analysis, and structural equation modeling analysis. The results revealed that academic procrastination had a significant negative impact on the readability indicator of Flesch-Kincaid Grade Level in L2 writing. L2 writing anxiety played a complete mediating role in the impact. Academic procrastination can significantly affect Flesch-Kincaid Grade Level of L2 writing indirectly through L2 writing anxiety. Pedagogical implications and future studies were discussed.